STRUCTURAL-LEVEL EVALUATION MODEL OF PREPAREDNESS OF CANDIDATES FOR ADOPTIVE PARENTS - Aldashseva, A. A.; Ponamareva , E. A.; Sapozhnikova , T. N. (Modern Psychology, 2019)
This article presents the theoretical and scientific-practical premises for developing a system of selection of candidates for adoptive parents for a reception in the family of children of a complex category, presents a structural-level model for assessing the preparedness of candidates for adoptive parents, and describes the procedure for selecting candidates for adoptive parents.
Keywords: adoptive parents, competence, selection, socio-psychological maturity, preparedness.